The Impact of Investment Climate Reforms on the Development of Small and Medium Sized Enterprises in Nigeria: A Policy Brief - Awan, Abdul Ghafoor; Khan, Rana Ejaz Ali (International Journal of Sustainable Development & World Policy, 2013)
Introduction: The 21st century was started with the dawn of a new economic puzzle of China’s fast economic growth. It has surprised the economists. The Chinese constant upward growth has shifted economic paradigm and the axis of growth appear to have been shifted from the western hemisphere to the eastern hemisphere. Some economists term it a 21st century miracle. The author has determined to test this miracle through empirical framework. Research Question: Main research question of this study to explore the answer of the question why China is recording consistent rapid economic growth? Is this growth in the same way as other developed countries experienced in the past or is it a new phenomenon-a shift in global economic paradigm. Objectives: The objective of this empirical analysis is to investigate into the causes of fast economic growth of China in the context whether this growth pattern is a normal phenomenon or an indicator of shifting global economic paradigm. Methodology: Our study is spread over a period starting from 1980 to 2011 because of the introduction of economic reforms and massive economic growth. We have collected data from different sources such as China Bureau of National Statistics, IMF, World Bank and relevant research Journals and books. The selected variables for this research paper are: labour productivity, investment, exports, Research and Development expenses, capital stock, open door policy, real exchange rate and US GDP. We used ordinary least square (OLS) model to measure change in the selected variables. Five tests were used to test the stability of the model. Findings: The Econometric results show that international trade and investment in capital stock and R&D expenses by Chinese Government are the major determinants, which are responsible for enhancing labour productivity and output in the long-run, Similarly, real exchange rate appears as an important determinant to explain change in output in the long-run.